تطبيق التعليم الإلكتروني في مؤسسات التعليم العالي وتأثيره في استدامة وتطوير وجودة وتسهيل العملية التعليمية في ظل الظروف الاستثنائية. - د. مهلة الزين بريمة أحمد (White Nile Journal for Studies and Research, 2025)
The study aimed at continuity, developing, quality and facilitating the educational process in higher education, which reflects positively on increasing academic achievement among students. In institutions of higher education and scientific research, as a result of not keeping pace with scientific and technical developments and the educational environment, in unprepared universities and not keeping pace with this development, in order to build a generation capable of dealing with the vocabulary of the modern era, and the research used the experimental and descriptive analytical method, and the study reached the most important results that education The electronic system leads to its continuity in all circumstances, improves performance, increases students' skills, and recognizes the developments of scientific technology in teaching methods and its modern tools, easy access to the required content, and saves time, effort, and cost for the teacher and the learner together. Teaching is like a tablet, smart board, e-mail, and electronic platform intention, the digital repository, the expansion of the database of data and information sources, and the interest in e-learning to expand students' perceptions and achievement. Keywords: Implementing of e-learning, in higher education institutions, continuty, development, quality, the educational process, forceful circumstances.